A Novel Visually Guided Radiofrequency Balloon Ablation Catheter for Pulmonary Vein Isolation: One-Year Outcomes of the Multicenter AF-FICIENT I Trial - Reddy, Vivek Y; Al-Ahmad, Amin; Aidietis, Audrius; Daly, Matthew; Melton, Iain; Hu, Yan; Sulkin, Matthew; Rackauskas, Gediminas; Ebner, Adrian; Hooks, Darren A; Sofi, Aamir; Neužil, Petr; et al. (Circulation. Arrhythmia and electrophysiology, 2021)
[Figure: see text].
Keywords: Equipment Design; dospělí; Surgery, Computer-Assisted; srdeční katétry; převodní systém srdeční; Recurrence; Female; fluoroskopie; Atrial Fibrillation; Pulmonary Veins; Adult; výsledek terapie; ženské pohlaví; Catheter Ablation; Time Factors; časové faktory; lidé; Fluoroscopy; recidiva; katetrizační ablace; Treatment Outcome; venae pulmonales; následné studie; prospektivní studie; Follow-Up Studies; Male; Aged; Prospective Studies; Heart Conduction System; fibrilace síní; lidé středního věku; senioři; mužské pohlaví; Cardiac Catheters; design vybavení; chirurgie s pomocí počítače; Middle Aged; Humans